Sinergitas Mahasiswa UIN Ar-Raniry Terhadap Syariat Islam (Analisis Terhadap Mahasiswa 5 Fakultas dalam Mata Kuliah Studi Syariat Islam di Aceh) - Mustaqilla, Safira (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Students from various faculties at the State Islamic University (UIN) have a strategic role in supporting the implementation and development of Islamic sharia in Aceh. This article explores the contribution of students from across faculties, including the Sharia, Tarbiyah (Education), Psychology, Da'wah, and Ushuluddin Faculties, in supporting the implementation of Sharia values through Islamic Sharia Studies Courses in Aceh (Studi Syariat Islam di Aceh). This research approach is descriptive qualitative, with data obtained through narratives of portfolio results in class. The research results show that each faculty makes unique contributions in accordance with their expertise. The Sharia Faculty plays a role in advocacy and socialization of sharia qanun. The Tarbiyah Faculty supports strengthening Islamic education through a sharia-based curriculum. The Faculty of Psychology offers an Islamic counseling approach that is relevant to supporting people's mental health. The Da'wah Faculty utilizes digital media to spread sharia values creatively, while the Ushuluddin Faculty strengthens understanding of Islamic teachings through in-depth academic studies. This cross-faculty collaboration creates significant synergy in strengthening the holistic implementation of Islamic sharia in Aceh, both from an educational, social and cultural perspective. This research recommends the development of a more integrated cross-faculty program to support the inclusive and sustainable implementation of Islamic sharia.